2021
DOI: 10.12659/msm.929092
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Structural and Functional Reorganizations Following Motor Stroke

Abstract: Background The combined effects of bilateral corticospinal tract (CST) reorganization and interhemispheric functional connectivity (FC) reorganization on motor recovery of upper and lower limbs after stroke remain unknown. Material/Methods A total of 34 patients underwent magnetic resonance imaging (MRI) examination at weeks 1, 4, and 12 after stroke, with a control group of 34 healthy subjects receiving 1 MRI examination. Interhemispheric FC in the somatomotor network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Furthermore, FA within PLIC in the acute phase was significantly correlated with clinical outcome at 90 days in peripheral infarcts, whereas no significant association was found for basal ganglia infarcts. Similarly, Xia and colleagues [ 33 ] reported a decline in FA values in the ipsilesional CST during the first week poststroke and then longitudinal increase over the next 12 weeks. Again, significant associations with clinical outcome were found after the acute phase.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Furthermore, FA within PLIC in the acute phase was significantly correlated with clinical outcome at 90 days in peripheral infarcts, whereas no significant association was found for basal ganglia infarcts. Similarly, Xia and colleagues [ 33 ] reported a decline in FA values in the ipsilesional CST during the first week poststroke and then longitudinal increase over the next 12 weeks. Again, significant associations with clinical outcome were found after the acute phase.…”
Section: Discussionmentioning
confidence: 82%
“…Three studies included additional imaging modalities, i.e., resting-state functional MRI (rs-fMRI) [ 26 , 32 , 33 ]. With regards to additional neurophysiological measures, only one study examined the functional integrity of the pyramidal tract using transcranial magnetic stimulation (TMS) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found an average increase of 6.9 points in the Fugl-Meyer scale after 15 days of therapy, which increased to 7.7 points 4 weeks after therapy and was significantly greater than the change observed in the sham group. Given that most of the cortical reorganization processes are expected to occur during the sub-acute phase post stroke (56), this may be the optimal window of recovery to be modulated by the implementation of VNS in combination with physical therapy, however, future clinical studies with larger sample sizes will be necessary to confirm whether earlier administration of this intervention is associated with greater improvement in motor function.…”
Section: Discussionmentioning
confidence: 99%
“…Resting-state brain networks during stroke recovery were initially assessed using functional magnetic resonance imaging (fMRI). According to studies on resting-state fMRI, stroke patients have different modes of functional connectivity compared with healthy people, and abnormal dynamic functional connectivity is associated with post-stroke motor recovery (4,(9)(10)(11). Although fMRI is the gold standard for measuring cortical activity, it has some drawbacks, such as restricted monitoring environments, acoustic scanner noises, subject head immobilization, and high cost (12).…”
Section: Introductionmentioning
confidence: 99%